The gems of Johor Bahru: revitalising Sungai Segget as a vibrant heritage and cultural riverfront - Syed Mohamad, Sharifah Mariana; Mohd. Hussain, Mohd. Ramzi; Zakariya, Khalilah (IIUM Press, 2024)
This project proposes the revitalisation of Sungai Segget as a vibrant heritage and cultural riverfront. Presently, the issues include the river condition in Class III and IV and less appreciation of the site's heritage values. The name Segget came from the English word "seagate", a structure prevalent in Johor in the 1900s. This 4,280-meter river has been labelled the second most polluted river in Malaysia. The awful stench emitted by the river was due to uncontrolled sewage management by business activities along the Segget River. The methods employed in this project are site inventory, analysis and synthesis for data collection, and design process for ideation and strategies. This project proposed strategies to revitalise Sungai Segget and the surrounding area through the concept of 'The Living Museum' and activating the site through the Blue Trails, Green Trails, Heritage Trails and improved accessibility.